Penguatan Sumber Daya Konselor Unggul di Era Digital - Muhamad Rozikan (Prosiding Seminar Nasional Pascasarjana, 2022)
Abstrak. Menjadi sebuah kenyataan bahwa era modern seperti saat sekarang ini, teknologi dan informasi yang berkembang saat ini akan memberikan peran dalam pengembangan yang sangat penting dalam peningkatan kehidupan manusia dan pertumbuhan perekonomian di masyarakat. Kemajuan tekonologi tersebut akan memberikan peluang bagi semua pihak dalam membagikan akses informasi dan teknologi. Tujuan dari penelitian ini adalah untuk menganilisis tentang penguatan sumber daya konselor di era digital. Metode penelitian ini menggunakan metode kepustakaan yang mana proses penelitian yang dikembangkan dengan metode mengumpulkan berbagai literatur dan catatan yang ada, yang berkaitan dengan data dan informasi. Adapun hasil penelitian ini adalah terdapat 7 (tujuh) type milenial yakni: 1) the adventurer; 2) the visionary; 3) the artist, 4) the leader, 5) the socializer6) the conservative, low profile, dan 7) the collaborator . Abstract. It becomes a fact that the modern era as it is today, technology and information that are developing today will provide a role in development which is very important in improving human life and economic growth in society. These technological advances will provide opportunities for all parties to share access to information and technology. The purpose of this study is to analyze the strengthening of counselor resources in the digital age. This research method uses a literature method which is a research proses developed by the method of collecting various existing literature and records, which are related to data and information. The results of this study are that there are 7 (seven) types of millennials, namely: 1) the adventurer; 2) the visionary; 3) the artist, 4) the leader, 5) the socializer6) the conservative, low profile, and 7 ) the collaborator .